Nisbah Berat Daun Dan Luas Daun Spesifik Tanaman Sawi Akibat Pemberian Pupuk Organik Di Tanah Gambut Kota Palangka Raya - Djoko Eko Hadi Susilo (Anterior Jurnal, 2014)
The purpose of this research is to know and analyze the weight area ratio and specific leaf area mustard green on the effect of organic fertilizer PETROGANIK on peat soil in Palangka Raya from January to March 2014 in Panarung, Palangka Raya. This experiment used single treatment with randomized complete design, each treatment was repeated ten times. The treatment consist of single factor is dose of giving organic fertilizer PETROGANIK (PO) in five levels : PO1 = 200 kg ha-1, PO2 = 400 kg ha-1, PO3 = 600 kg ha-1, PO4 = 800 kg ha-1 and PO5 = 1.000 kg ha-1. Variable response of this research is a high plant, number of leaves, leaf area, weight area ratio, specific leaf area, and fresh yield of mustard green on 28 days after planting. The experiment resulted, showed that organic fertilizer PETROGANIK nonsignificant to high plant, number of leaves, leaf area, weight area ratio and specific leaf area but significant and can increase the fresh yield of mustard green. Although organic fertilizer PETROGANIK nonsignificant to weight area ratio and spesific leaf area mustard green, but its an alternative variable to describing plant growth and correlation with a fresh yield of mustard green. Application 1.000 kg ha-1 organic fertilizer PETROGANIK is the best treatment to increase growth plant and yield mustard green on peat soil.